HYPOGLYCEMIC EFFECT OF POLYHERBAL FORMULATIONS IN ALLOXAN INDUCED DIABETIC MICE - Srivastava, Noopur; Rai, Awani K. (Journal of Drug Delivery and Therapeutics, 2018)
Objective: The present work was executed to evaluate the antidiabetic potency of herbal preparation which was the combination of wheat germ oil, fresh juice of CorianderÂ sativumÂ and Aloe vera gel in normal andÂ alloxan-inducedÂ diabetic mice. Methods: TheÂ serum glucose lowering activity of the herbal preparation (PH-1 in the ratio of 1:1:1of wheat germ oil, fresh juice of C.sativum and Aloe vera) was studied in normal rats after oral administration at 1.0 and 2.0ml/kg and herbal preparation (PH-1, PH-2 wheat germ oil, fresh juice of coriander sativum and Aloe vera gel in ratio of 2:2:1) and PH-3 (wheat germ oil, fresh juice of coriander sativum and Aloe vera gel in ratio of 1:2:2) on alloxan induced diabetic swiss albino mice, at doses of 1.0 and 2.0 ml/kg. Blood samples were collected and analyzed for serum glucose at 0,1/2, 1, 2, 4, 8, 12 and 24 h in normal mice and at 0, 1, 3, 7, 15 and 30 days in diabetic mice after drug administration by glucose oxidase/peroxidase method. The data were compared statistically by using one way ANOVA method followed by Dunnett multiple componentÂ test. Statical significance was set at p<0.05. Results: TheÂ herbal preparation (1.0 and 2.0 ml/kg) produced significant (p<0.05) reduction in serum glucose level of both normal and diabetic mice and comparable with that of control and standard drug Glibenclamide. Conclusion: TheÂ herbal preparation showed significant glucose lowering effect in normal and alloxan induced diabetic rats. This preparation is giving to be a promising antidiabetic preparation for masses and however, it requires further extensive studies in human beings. Keywords: Antidiabetic potency, alloxan-induced diabetic rats, Aloe vera